2014
DOI: 10.1371/journal.pone.0086915
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Stain Plus MALDI-TOF MS (Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry) for a Rapid Diagnosis of Urinary Tract Infection

Abstract: Microbiological confirmation of a urinary tract infection (UTI) takes 24–48 h. In the meantime, patients are usually given empirical antibiotics, sometimes inappropriately. We assessed the feasibility of sequentially performing a Gram stain and MALDI-TOF MS mass spectrometry (MS) on urine samples to anticipate clinically useful information. In May-June 2012, we randomly selected 1000 urine samples from patients with suspected UTI. All were Gram stained and those yielding bacteria of a single morphotype were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 41 publications
4
59
0
6
Order By: Relevance
“…The negative predictive and positive predictive values were 98.1% and 70.5% respectively. This finding was in Similar to a study by Almudena Burillo et al 15 In the present study we observed a high specificity and negative predictive values for gram staining of urine signifying it as a useful screening test for bacteriuria in resource constraint situations where culture facilities are not available .Nevertheless the limitation could be that it requires trained personnel to screen and interpret the results and observer variation may also occur in interpreting the result. Studies have reported the sensitivity and specificity of Gram staining of urine varying from 80-99%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The negative predictive and positive predictive values were 98.1% and 70.5% respectively. This finding was in Similar to a study by Almudena Burillo et al 15 In the present study we observed a high specificity and negative predictive values for gram staining of urine signifying it as a useful screening test for bacteriuria in resource constraint situations where culture facilities are not available .Nevertheless the limitation could be that it requires trained personnel to screen and interpret the results and observer variation may also occur in interpreting the result. Studies have reported the sensitivity and specificity of Gram staining of urine varying from 80-99%.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have reported the sensitivity and specificity of Gram staining of urine varying from 80-99%. 2,15 Our study have found a high specificity (96.29%), high NPV (98.11%) for Pus cell count similar to the study by Sushma thakre. 9 In the present study Escherichia coli 5 (38.4%) was the most common bacteria isolated.…”
Section: Discussionsupporting
confidence: 86%
“…Direct analysis of clinical samples further increased the usefulness of this method by eliminating the time required for microorganism growth and isolation. Several studies have applied the technique to detect and identify microbial pathogens directly from urine (10)(11)(12)(13) and have revealed that clinicians would receive therapeutically helpful information for 96.1% of samples in less than 1 h (10,14).…”
mentioning
confidence: 99%
“…Much effort has been spent to improve urine processing and to enhance the identification capability of MALDI-TOF MS by coupling it with rapid urine analysis (4,10,12,(14)(15)(16). This study aimed to establish and optimize a urine processing method to improve the analytical sensitivity and specificity of MALDI-TOF MS.…”
mentioning
confidence: 99%
“…La concordancia entre la identificación de microorganismos por ambos métodos fue del 90,0% en las muestras monomicrobianas, mientras que en las muestras de orina con dos microorganismos, el MALDI-TOF MS pudo identificar ambos microorganismos en el 9,0% de los casos. Así mismo, Burrillo y colaboradores 43 evaluaron el uso conjunto de la tinción de gram y la identificación por el espectróme-tro de masas Microflex LT (Bruker Daltonics Inc.) en muestras de orina, encontrando que en el 82,7% de los casos se obtuvo un resultado anticipado al obtenido por cultivo, con 13,4% de errores menores y 3,9% de errores mayores. Aunque el impacto clínico de estas estrategias debe ser evaluado a través de indicadores referentes a la terapia antimicrobiana, se puede inferir su impacto potencial al proveer resultados de identificación de microorganismos en el transcurso de una hora.…”
Section: Orinaunclassified